Development and characterization of a Versatile Engineered Nanomaterial Generation System (VENGES) suitable for toxicological studies - Demokritou, Philip (Inhal Toxicol, 2010)
A novel system for generation of engineered nanomaterials suitable for in situ toxicological characterization within biological matrices was developed. This Versatile Engineered Nanomaterial Generation System (VENGES) is based on industry-relevant, flame spray pyrolysis (FSP) aerosol reactors that can scaleably produce engineered nanomaterials (ENMs) with controlled primary and aggregate particle size, crystallinity and morphology. ENMs are produced continuously in the gas phase, allowing their continuous transfer to inhalation chambers, without altering their state of agglomeration. Freshly generated ENMs are also collected on Teflon filters for subsequent physico-chemical and morphological characterization and for in vitro toxicological studies. The ability of the VENGES system to generate families of ENMs of pure and selected mixtures of iron oxide, silica and nanosilver with controlled physico-chemical properties was demonstrated using a range of state-of-the-art-techniques. Specific surface area was measured by nitrogen adsorption using the Brunauer-Emmett-Teller (BET) method, and crystallinity was characterized by X-ray diffraction (XRD). Particle morphology and size were evaluated by scanning and transmission electron microscopy (STEM/TEM). The suitability of the VENGES system for toxicological studies was also shown in both in vivo and in vitro studies involving Sprague-Dawley rats and human alveolar-like monocyte derived macrophages, respectively. We demonstrated linkage between physico-chemical ENM properties and potential toxicity.